Social media and youth: the risk of radicalization - A.D. Tikhonova (Психология и право, 2018)
The purpose of this article is the socio-psychological analysis of the process of radicalization of young people through the use of social media. The article considers the role of social networks in the life of modern youth, touches upon the problem of "clip" consciousness in the perception of media space, and analyzes the features of the radicalization process through the use of modern media platforms such as Twitter, Facebook.It is noted that online chats today are a key tool for radicalization of young people. It is emphasized that social media contribute to the fact that young people have a distorted picture of the world, which ultimately contributes to the loss of a sense of self-identification and the emergence of uncertainty. Extremism and radicalization are considered as a way to overcome uncertainty in the modern world, as well as an attempt to solve the lack of time. The article discusses that the state of boredom and a sense of uncertainty are fertile ground for radicalization of young people.